The Relationship between Healthy Life Behavior (Knowledge, Attitude, and Practice) with the Occurrence of Scabies in Daarul Quran Islamic Boarding School Surakarta - Astrid Astari Aulia; Nurrachmat Mulianto; Suci Widhiati (Nexus Kedokteran Komunitas, 2017)
Introduction: Healthy life behavior is knowledge, attitudes, and practice to maintain healthy condition and prevent disease, as well as an active role in public health movement. The high prevalence of scabies in boarding school in Indonesia is influenced by lack of knowledge about scabies. Data from Daarul Quran Islamic Boarding Schools health center during the period of February-August 2015 show that there were 40 students from total of 162 (24.6%) students who at least once been infected by scabies. Based on the explanation above, researchers interested in conducting a study to determine the relationship between healthy behavior which consist of knowledge, attitudes, and practices with the occurance of scabies in Daarul Quran Islamic Boarding School Surakarta. Methods: This study was an observational analytic with cross-sectional approach. A total of 155 students of Daarul Quran Islamic Boarding School Surakarta involved as research subjects. The dependent variable in this study was the occurance of scabies while the independent variables consist of knowledge, attitudes, personal hygiene and habits. Independent variables were measured using a questionnaire. The variables were analyzed by bivariate analysis using chi-square test. Result: There were 59 (38,1%) from 155 students of Daarul Qur'an Surakarta Islamic Boarding School infected by scabies. A number of 31 (52.5%) of the total 59 infected students aged 13 years. Most of the students exposed to scabies still in 7th grade (55.9%). Bivariate analysis showed that there was a significant relationship between knowledge (p = 0.021), attitude (p = 0.029), action (personal hygiene (p = 0.024) and habits (p = 0.024)) with occurence of scabies in Pondok Pesantren Daarul Qur 'an Surakarta. Conclusions: There is a relationship between healthy life behavior (knowledge, attitudes, and practices) and scabies occurrence in Daarul Qur'an Islamic Boarding School Surakarta, therefore more effective promotion and health education is needed to lower scabies incidence. Keywords: Scabies, Healthy Life Behavior, Knowledge, Attitude, Practices